Arqueologia pública: uma reflexão sobre arqueologia e patrimônio cultural a partir da interação com a sociedade - Santos, Taislayne Maria Ferreira (2023)
The present research addresses public archaeology through interaction with society, where individuals' involvement with the discipline lies in the pursuit of preservation and protection of cultural heritage. In order to do so, the following question is raised: how do public archaeology and society relate to each other in promoting the protection and preservation of archaeological and cultural heritage? Thus, the main objective is to analyze public archaeology and its relationship with society from an academic perspective through a literature review, focusing on strategies for the preservation and protection of cultural and archaeological heritage. Therefore, the specific objectives are: to present conceptual and historical characteristics of public archaeology; to explain archaeological praxis and the social role of the archaeologist; to highlight cultural, archaeological, and historical heritage in identifying their differences through characteristics and/or archaeological legislation; and, finally, in the results and discussions section, the systematic review of references is presented, which resulted in the production of this research, and to examine projects and archaeological programs in the state of Sergipe related to public archaeology, as well as studies that emphasize its importance. The choice of this theme is the result of the need to understand the role of the archaeologist, how society perceives our work, and the means by which they can also actively participate. The idea is for the research to have social and cultural relevance for professionals in the fields of social sciences such as archaeology, sociology, museology, geography, history, and others. In summary, the research has a basic nature, the approach is exploratory in order to gain greater familiarity. According to the method, it has a bibliographic approach, as it used books, articles, monographs, and documentary sources. Finally, the aim was to analyze the data collected regarding archaeological projects and public archaeology in the quest for problem resolution.